Children's Education in the Metaverse Era: Between the Rapid Growth of Information Technology and Self-learning of Generation Z - Saifuddin Chalim; Fadly Usman; Mauhibur Rokhman; Ibnu Rusydi; Rahmat; Bahrudin Zamawi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
The phenomenon of distance learning patterns during the pandemic has become an extraordinary leap and has significantly impacted the massive use of the internet in society. The digital era is an era where many human life activities are carried out online by minimizing social interaction, such as school with online learning, working in the office to working from home, organizational meetings via online meeting platforms such as Zoom and Google Meet, health consultations answered directly by doctors, as well as other activities that were rarely carried out before Covid-19. This research aims to determine children's learning patterns and behavior in the metaverse era. Meanwhile, the research method used is quantitative, with several approaches such as correlation between variables and the close relationship between one variable and another. The three groups of respondents in the study were early adults (>20 years), early adolescents (15-20) years and children (10-15 years). The research results show that at the age of children, smartphone use and online activities are only limited to playing games and social media. Meanwhile, in their early teens, some are even starting to learn game-making through online platforms such as Roblox Studio. In early adulthood, which is the age of college education, smartphone use is not just about social media or online shopping; some even have digital wallets and crypto wallets, invest in cryptocurrency, and even actively use the creator's platform games and NFTs with payments via cryptocurrencies such as Ethereum, polygon, etc.